AB0554 Factors affecting quality of life in indian patients with systemic lupus erythematosus. (12th June 2018) - Pinto, B.; Grover, S.; Rathi, M.; Dhooria, A.; Sharma, A.
Abstract : Background: SLE has a profound impact on Quality of Life (QoL). In addition to disease activity and damage, other factors such as fatigue, fibromyalgia and psychiatric comorbidities also influence QoL. 1 However, there is lack of data in the form of comprehensive assessment of all these factors in the same cohort. Objectives: To assess the quality of life and its correlates among patients with SLE. Methods: Using a cross-sectional study design, 144 patients with SLE were assessed for disease activity and damage by using SELENA –SLEDAI and SLICC/ACR damage Index (SDI)), depression (by using Patient Health Questionnaire-9 (PHQ9), anxiety (by using Generalised Anxiety Disorder 7 (GAD7)), fatigue (by using Fatigue severity scale (FSS)) and fibromyalgia (as per using ACR 2010 criteria). QoL was assessed using a generic Qol scale – Short Form 36 (SF-36).2 Statistical analysis was done using STATA version 14. Results: The study sample included 140 females and 4 males. Mean age of the participants was 32.48 (SD-7.26) years and the mean duration of illness was 3.92(SD-3.76) years. The mean SELENA SLEDAI and SDI was 3.42±4.04 and 0.26±0.65 respectively. Prevalence of depression (PHQ9 ≥10) and anxiety (GAD7 ≥10) was 25% and 22.9% respectively. Fatigue (FSS ≥4) was present in 51.4%. Physical domains of SF36 were affected more often than the mental domains, 71.5% of the respondents had scores less than 50 in Physical component Summary (PCS) and 61.1% in Mental Component Summary (MCS) of SF36. No correlation was found between disease activity and damage and various domains of SF36. Depression, anxiety and fatigue had a significant negative correlation with all the domains of SF36 (table 1). On multivariate regression only fatigue was an independent predictor of PCS of QoL. Conclusions: Fatigue, depression and anxiety have a greater influence on QoL in SLE than disease activity and damage. Of these, fatigue appears to be the most important variable which influences QoL. References: [1] Schmeding A, Schneider M. Fatigue, health-related quality of life and other patient-reported outcomes in systemic lupus erythematosus. Best Pract Res Clin Rheumatol. 2013;27(3):363–375. [2] Maruish ME (Ed). NEW SF36v2 User Guide, 3rd Edition .; 2011. Acknowledgements: Mr. John Michael Raj, Department of Biostatistics, St. John's National Academy of Health Sciences, Bengaluru Disclosure of Interest: None declared